Drugs Compromising Male Sexual Health - Krause, Walter K.H (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Written by an acknowledged and experienced expert in the field, this concise drug guide lists approximately 500 substances, such as pharmaceutical drugs, lifestyle drugs, and environmental toxicants, that show documented untoward effects on the male sexual organs and their functions. All substances are listed in user-friendly alphabetical order and each listing: Provides more detailed information on each drug than any other standard pharmacology title Includes references quoting the necessary details of each study Shows important relationships between a disturbance of male sexual function and a drug's adverse side effects. This unique guide has the potential to greatly improve your treatment outcome. Knowledge of the relevance of undesirable drug effects will allow physicians working in the fields of andrology and reproductive medicine to find and eliminate the underlying cause of male sexual health disorders.